2012
DOI: 10.1111/j.1349-7006.2012.02213.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of 5‐hydroxymethylcytosine is accompanied with malignant cellular transformation

Abstract: Dysregulated DNA methylation followed by abnormal gene expression is an epigenetic hallmark in cancer. DNA methylation is catalyzed by DNA methyltransferases, and the aberrant expression or mutations of DNA methyltransferase genes are found in human neoplasm. The enzymes for demethylating 5-methylcytosine were recently identified, and the biological significance of DNA demethylation is a current focus of scientific attention in various research fields. Ten-eleven translocation (TET) proteins have an enzymatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
211
4
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(234 citation statements)
references
References 40 publications
(96 reference statements)
14
211
4
5
Order By: Relevance
“…global DNA hypomethylation complicated by regional hypermethylation (31,32) and up-regulated expression of the DNMTs including DNMT3A and DNMT3B (31,33), are frequently observed. The environment of the cancer cells, in particular the presence of oxidative stresses, likely would facilitate 5-mC oxidation (18,34) as well as the dehydroxymethylase activities of DNMT3A/3B, thus leading to a profound reduction of the 5-hmC level (35)(36)(37) and also causing global hypomethylation of the cancer genomes (31,32). In this aspect, it seems like that the de novo DNMTs serve a protective function when cells are under oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…global DNA hypomethylation complicated by regional hypermethylation (31,32) and up-regulated expression of the DNMTs including DNMT3A and DNMT3B (31,33), are frequently observed. The environment of the cancer cells, in particular the presence of oxidative stresses, likely would facilitate 5-mC oxidation (18,34) as well as the dehydroxymethylase activities of DNMT3A/3B, thus leading to a profound reduction of the 5-hmC level (35)(36)(37) and also causing global hypomethylation of the cancer genomes (31,32). In this aspect, it seems like that the de novo DNMTs serve a protective function when cells are under oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, like 5mC alterations, the 5hmC patterns undergo considerable changes linked to genome instability (70,71) across several forms of human cancers (72). Recent studies revealed that 5hmC is consistently found at significantly reduced levels (more than 50% reduction, p ≤ 0.01) in various solid tumors (73)(74)(75). Recently, using a mouse model, Pan et al (76) studied the role of hydroxymethylation in neurophysiological processes and provided the first evidence that miRNAs can be regulated by hydroxymethylation of their promoters.…”
Section: Dna Hydroxymethylationmentioning
confidence: 99%
“…There are three TET genes in mammalian cells: TET1, TET2 and TET3 (Pastor et al, 2013). Furthermore, deregulation of the three proteins were accompanied by some diseases such as cancers (Kudo et al, 2012;Lian et al, 2012). TET1 act as tumor suppressors regulating cancer development, growth and invasion (Mercher et al, 2012;Ciccarone et al, 2014).…”
Section: Introductionmentioning
confidence: 99%